No Country for Old Hippies: Jason Mellard's Progressive Country (Southern Spaces, 2014)
Stephanie Vander Wel reviews Jason Mellard\'s Progressive Country: How the 1970s Transformed the Texan in Popular Culture (Austin, Texas: University of Texas Press, 2013).